Worlds Apart: Island Identities and Colonial Configurations in the Dutch Caribbean - Jessica Vance Roitman; Wouter P. Veenendaal (Island Studies Journal, 2023)
Analyses of the Caribbean continue to divide the region based on colonial heritage, which is largely a result of the fact that it primarily consists of small islands. In this article, we demonstrate the inaccuracy of such categorizations on the basis of two sets of arguments. Based on historical as well as contemporary evidence from the Dutch Caribbean, we show that different islands that were artificially united into a single jurisdiction by colonial powers commonly experience intense inter-island rivalries and separatist tendencies. In addition, however, we show evidence pointing to frequent contacts and shared regional identities between neighboring islands belonging to different (post)colonial spheres of influence, both in the past and in the present. In sum, therefore, our interdisciplinary analysis -- combining insights from history and political science -- shows that small islands experience seemingly contradictory tendencies towards both island nationalism and inter-island cooperation, but that cooperation can only work if it is initiated on the terms of islands themselves, and not determined by colonial rulers or metropolitan states.